2016
DOI: 10.1002/ijop.12397
|View full text |Cite
|
Sign up to set email alerts
|

The role of attentional resources in explaining sex differences in object location memory

Abstract: Sex differences in object location memory have been widely studied, with mixed results. The role of attention in mediating the female advantage in object location memory has not been clearly understood yet. Two experiments, involving 181 participants and using an actual object array, were conducted in the present study to examine two learning conditions: incidental and intentional. In each experiment, participants were randomly assigned to divided versus full attention conditions. The study also examined memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…In this study, women retained memory performance even when performing a parallel task that was presumed to compete for attentional resources. The current results contradict previous attempt to establish female superiority in object location memory under divided attention condition (Barel, ). However, the current study differs from the previous one in two ways: first, the presentation of physical object array versus an array presented on paper, and second, the use of an arithmetic task versus tone discrimination as a distraction task in the former versus the present study, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In this study, women retained memory performance even when performing a parallel task that was presumed to compete for attentional resources. The current results contradict previous attempt to establish female superiority in object location memory under divided attention condition (Barel, ). However, the current study differs from the previous one in two ways: first, the presentation of physical object array versus an array presented on paper, and second, the use of an arithmetic task versus tone discrimination as a distraction task in the former versus the present study, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, studies differed in other task characteristics, recognition of location‐exchanged (the number of correct detection of objects exchanging locations) and location‐maintained (the number of correct detection of objects maintaining locations). Honda and Nihei () and Barel () shown that female advantage was observed only in memorising location‐exchanged objects.…”
Section: Sex Differences In Object Location Memorymentioning
confidence: 99%
See 3 more Smart Citations